Early evaluation of adjuvant effects on topramezone efficacy under different temperature conditions using chlorophyll fluorescence tests - Zhang, Jinwei; Xie, Yaqiong; Zhang, Chunhua; Zhang, Peng; Jia, Chunhong; Zhao, Ercheng (Frontiers in Plant Science, 2022)
Proper selection of adjuvant applications is an important strategy to enhance herbicide efficacy and reduce active ingredient input especially under adverse environmental conditions. In this study, a two-factor split-plot-design experiment was conducted to evaluate the effects of two adjuvants on the efficacy of topramezone on the grassy weed species giant foxtail (Setaria faberi Herrm.) and the broadleaved weed species velvetleaf (Abutilon theophrasti Medik.) under three different temperature conditions. The two tested adjuvants were methylated seed oil (MSO) and organosilicone. Three temperature levels, 35/30C, 25/20C, and 15/10C (day/night), were used in the laboratory and greenhouse experiment. Plant chlorophyll fluorescence measurements shortly after herbicide application and classic whole-plant bioassay methods were used to evaluate the herbicide efficacy among the different treatments. The results indicated that the maximum quantum efﬁciency (Fv/Fm) of the top leaf of the weeds treated with topramezone mixed with MSO was signiﬁcantly lower than that of the weeds treated with topramezone mixed with organosilicone and without an adjuvant at 2–3 days after treatment under all three temperature levels. The herbicide response of the plants treated with topramezone mixed with organosilicone and topramezone alone was not significantly different. These results corresponded well with the results of the classic whole-plant test. MSO has been shown to be good at enhancing the efficacy of topramezone on these weed species under all three temperature conditions. The measurement of chlorophyll ﬂuorescence is a promising technique for evaluating the effects of adjuvants on the efﬁcacy of herbicides shortly after herbicide treatment.